2022
DOI: 10.1017/ash.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Ward-level risk factors associated with nosocomial coronavirus disease 2019 (COVID-19) outbreaks: A matched case–control study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic made its way from private, public, and work spaces into healthcare systems all over the world, imposing an unexpected burden on global health care. COVID-19 outbreaks in acute-care hospitals are a frequent problem, increasing morbidity and mortality among patients and leading to staff shortages. 1,2 Prevention of nosocomial severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) transmission in acute-care hospitals represents a major challenge. One importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Furthermore, Thoma et al showed that the only factor associated with occurrence of nosocomial COVID-19 outbreaks was an increased number of infected HCWs shortly before the outbreak. This finding supports that infected HCWs are an important source of nosocomial COVID-19 [42] . In addition, Abbas et al , who modelled the dynamic transmission of SARS-CoV-2 by combining epidemiological and genetic sequencing data, found that events with a higher rate of patient-to-patient transmission involved patients hospitalized in the same ward [43] .…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, Thoma et al showed that the only factor associated with occurrence of nosocomial COVID-19 outbreaks was an increased number of infected HCWs shortly before the outbreak. This finding supports that infected HCWs are an important source of nosocomial COVID-19 [42] . In addition, Abbas et al , who modelled the dynamic transmission of SARS-CoV-2 by combining epidemiological and genetic sequencing data, found that events with a higher rate of patient-to-patient transmission involved patients hospitalized in the same ward [43] .…”
Section: Discussionsupporting
confidence: 80%
“…For most nosocomial infections, the most likely source of infection was captured by between-ward dynamics, suggesting that the patient pathway implemented was successful in separating susceptible patients from infectious patients. This finding is supported by several other studies which found that healthcare workers were a likely source of nosocomial infection [13, 26, 27]. Evans et al found that indirect transmission from infected patients was the most likely route for nosocomial transmission, where indirect transmission may happen through healthcare workers acting as vectors for transmission or through fomite transmission [7].…”
Section: Discussionsupporting
confidence: 59%
“…Our study is one of several observational studies exploring risk factors for patient COVID-19 acquisition in hospitals [25][26][27][28][29][30][31][32]. There were several factors which were identified during this outbreak in a setting without vaccination for any HCWs or patients which may have facilitated the transmission events to occur.…”
Section: Discussionmentioning
confidence: 98%
“…Based on our findings, patients who spent > 50% of their admission in a multi-bedded room had 3.2 times the rate of acquiring COVID-19. Other observational studies have demonstrated that multi-bedded rooms versus one-to-two bedded rooms and the use of shared toilets were more common among nosocomial COVID-19 cases compared to controls [ 29 , 31 , 34 , 35 ]. The duration of time in a multi-bedded room was a major risk factor and the finding of a dose–response relationship adds epidemiologic strength of association to this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation